CRE: A Systematic Method for COTS Components Selection - Alves, Carina; Castro, Jaelson (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2001)
The market interest in developing reliable and stable products at shorter development time and reduced cost, has led to an increasing surge of interest in Component-Based Software Engineering. The success of these systems largely depends on the effective selection of components that meet users requirements. In this context, the products evaluation needs to be a simultaneous process with the requirements acquisition. This paper presents the CRE Method (COTS-Based Requirements Engineering), which is centered on requirements to assist the COTS selection process. The selection of medical packages is used as a case study.